The lady of Bolton Hill - Camden, Elizabeth, 1948- (Minneapolis, Minn. : Bethany House, 2011)
Female journalists are rare in 1879, but American-born Clara Endicott has finally made a name for herself with her provocative articles championing London's poor. When the backlash from her work forces a return home to Baltimore, Clara finds herself face-to-face with a childhood sweetheart who is no longer the impoverished factory worker she once knew. In her absence, Daniel Tremain has become a powerful industry giant and Clara finds him as enigmatic as ever. However, Daniel's success is fueled by resentment from past wounds and Clara's deeply-held beliefs about God's grace force Daniel to confront his own motives. When Clara's very life is endangered by one of Daniel's adversaries, they must face a reckoning neither of them ever could have foreseen.
Keywords: Women journalists -- Fiction; Bolton Hill (Baltimore, Md.) -- Fiction; Love stories; Historical fiction; Christian fiction